Contenidos de la publicidad televisiva y su influencia en las amas de casa del barrio la Cruz, parroquia Aloasí, cantón Mejía, provincia de Pichincha - Quicaliquín Guanochanga, Bárbara Karina (2015)
The advertising content and how to influence the decision to buy in the housewives in the La Cruz neighborhood, Aloasí parish, Mejía Canton, Pichincha province, it became the subject of this investigation work, whose motivation is produced from the need to give housewives of La Cruz neighborhood, an insight saving when buying. We studied the spots on television because is one means with more consumption, especially because is considered for entertainment. It have seen convenient work quantitatively through surveys and qualitative by interviews and focus groups, to determine whether television advertising meets the objective; in persuading housewives for products consumption, who watch over the family finances. Then a communications campaign called "Tips to save the pocket of your home" which seeks to change consumption habits, sample playful way possible to save around using homemade products, to replace existing on the market products, and present ways to save with the purchase of cheaper products.